Early clinical outcomes of all-inside arthroscopic anterior cruciate ligament reconstruction with autograft tendon augmentation using the LARS internal brace ligament - Wenlong, Huang; Maosheng, Yang; Hanbin, Wang; Yi, Li (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveThe aim of this study was to compare the early clinical outcomes of all-inside anterior cruciate ligament (ACL) reconstruction using hamstring tendons augmented using the ligament augmentation and reconstruction system (LARS) versus hamstring tendons alone as a control.MethodsThis study included 99 patients with ACL injuries who underwent all-inside arthroscopic ACL reconstruction using either the LARS internal brace ligament combined with hamstring tendon (augmentation group, n = 48) or hamstring tendon alone (hamstring group, n = 51). Postoperative follow-up was conducted using Lysholm, International Knee Documentation Committee (IKDC), Tegner, KOS-ADLS, and ACL-RSI scores to evaluate functional recovery of patients at 1, 3, and 6 months. If necessary, MRI findings obtained at postoperative 3 months were also analyzed to evaluate graft integration and healing dynamics. Tensile strength of the augmented graft was measured through tensile testing. Moreover, to evaluate the postoperative healing status of the augmented tendon, an ACL reconstruction model was established using New Zealand white rabbits. At 4 and 8 weeks postimplantation, rabbit knees were harvested, decalcified, embedded in paraffin, and stained to evaluate new tissue formation. All statistical analyses were conducted using the GraphPad Prism and SPSS software, with appropriate statistical tests applied for comparison between groups.ResultsAt 1-month postoperative follow-up, the LARS augmentation group demonstrated significantly higher Lysholm, IKDC, and KOS-ADLS scores than the hamstring group, with P < 0.01 for all comparisons. At 3-month postoperative follow-up, the augmentation group exhibited significantly higher Tegner, Lysholm, IKDC, and KOS-ADLS scores than the hamstring group, with P < 0.05 for all measurements. In the tensile testing, the tendons + LARS and LARS groups showed significantly higher maximum loads and lower elongation than the tendon group with P < 0.001 for maximum load and P < 0.05 for elongation. Examination of the histological sections at 4 and 8 weeks showed that the LARS ligament exhibited excellent biocompatibility, with abundant collagen fibers and neovascularization identified between its fibers.ConclusionThe combination of LARS internal brace ligaments with autograft tendons in ACL reconstruction provides superior early postoperative outcomes, improving knee stability and patient satisfaction with no remarkable complications. The augmented graft exhibited reliable tensile strength and favorable tissue integration.